STUDY ON WEBTOON AS MEDIA TO PROGRESS STUDENT READING SKILL AT THE SECOND GRADES OF SMAN 3 BANGKALAN - Nurrahman, Muawwanah; Wahyudi, Mohammad Arief (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study explores the effectiveness of Webtoon as a learning medium to improve reading skills and vocabulary development of students in grade XI at SMAN 3 Bangkalan. Using a qualitative descriptive approach, data were collected through classroom observations, student interviews, and documentation analysis. Findings indicate that Webtoon significantly increased students’ engagement, motivation, and comprehension compared to traditional textbooks. The combination of visual storytelling and contextual learning helped students better understand the text and acquire new vocabulary. Interview results showed that students often found and actively searched for the meaning of new words, which strengthened their language skills. Teachers acknowledged the advantages of Webtoon but highlighted challenges such as the use of slang and maintaining student focus. Despite these obstacles, Webtoon remains a valuable tool for improving literacy. This study concludes that Webtoon is an innovative and engaging medium for improving reading skills, and future research should explore strategies to optimize its use in education